The Influence of Price Perception, Location, and Word of Mouth on Purchasing Decisions at UMKM Ayam Penyet Meranti in Medan - Lubis, Nadia Utami; Mubarak, Husni (Program Pascasarjana STIE Amkop Makassar, 2024)
UMKM actors often feel a decrease in revenue turnover can be caused by a decrease in the level of purchase decisions that occur and by several factors. The purpose of this study was to determine the influence of price perception, location and word of mouth on purchasing decisions at UMKM Ayam Penyet Meranti in Medan. This research method is quantitative. The population of this study were all consumers who made a purchase on chicken penyet meranti in June. The number of samples in this study is 315 respondents. Data analysis techniques used in this study using SPSS software. Sample technique in this study using non probability sampling techniques. The nonprobability sampling method used is accidental sampling. The results of this study stated that the perception of price, location, and Word of Mouth have a positive and significant influence on purchasing decisions on chicken penyet meranti in Medan. as evidenced by the price variable has a value of 2,173 ttitung > ttable 1,650 and the value of GIS. 0.000 < 0.05. The location has a value of 3,193 > t table and 1,650 TG value. 0.002 ttabel1.650and the value of GIS. 0.000